Unanticipated Rapid Remission of Refractory Bulimia Nervosa, during High-Dose Repetitive Transcranial Magnetic Stimulation of the Dorsomedial Prefrontal Cortex: A Case Report - Downar, Jonathan; Sankar, Ashwin; Giacobbe, Peter; Woodside, Blake; Colton, Patricia (Frontiers in Psychiatry, 2012)
A woman with severe, refractory bulimia nervosa (BN) underwent treatment for comorbid depression using repetitive transcranial magnetic stimulation (rTMS) of the dorsomedial prefrontal cortex (DMPFC) using a novel technique. Unexpectedly, she showed a rapid, dramatic remission from BN. For 5 months pre-treatment, she had reported two 5-h binge-purge episodes per day. After rTMS session 2 the episodes stopped entirely for 1 week; after session 10 there were no further recurrences. Depression scores improved more gradually to remission at session 10. Full remission from depression and binge-eating/purging episodes was sustained more than 2 months after treatment completion. In neuroimaging studies, the DMPFC is important in impulse control, and is underactive in BN. DMPFC–rTMS may have enhanced the patient’s ability to deploy previously acquired strategies to avoid binge-eating and purging via a reduction in her impulsivity. A larger sham-controlled trial of DMPFC–rTMS for binge-eating and purging behavior may be warranted.